English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1. r^2/ r^2-s^2 multiplied by r-s/r+s divided by (r/r+s)^2

2.(2p-7/9)^3 divided by (7-2p/3)^4


Thanks everybody!! :)

2007-01-11 07:08:59 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

a. Factor everything.
b. ÷ a/b means the same as × b/a
c. multiply across numerators for solution numerator; multiply across denominators for solution denominator
d. (a²-b²) = (a+b)(a-b)

1. r² * (r-s) * (r+s)² ÷ (r+s)(r-s) *(r+s) * (r²)
everything cancels, so the answer is 1

2.. (2p-7)^3 * 3^4 ÷ 9^3 * (7-2p)^4

a. (a-b) = -(b-a)
b. 9 = 3²
c. (a^b)^c = a^(b*c)

-(7-2p)^3 * 3^4 ÷ 3^6 * (7-2p)^4

-1 ÷ 3²(7-2p)
or
1 ÷ 9(2p-7)

2007-01-11 07:24:31 · answer #1 · answered by bequalming 5 · 1 0

1. r^2/ r^2-s^2 multiplied by r-s/r+s divided by (r/r+s)^2
r^2/(r-s)(r+s)8(r-s)/(r+s)*(r+s)^2/r^2 =1

2.(2p-7/9)^3 divided by (7-2p/3)^4
= [(18p-7)/9]^3 / [(21-2p)/3]^4
= (18p-7)^3/9^3 * 3^4/(21-2p)^4
(18p-7)^3/9(21-2p^4)

2007-01-11 15:30:33 · answer #2 · answered by ironduke8159 7 · 0 0

1.
r^2(r - s)(r + s)^2
--------------------- = 1 (everything cancels out)
(r^2 - s^2)(r + s)r^2

2.
(((2p - 7)/9)^3)/((7 - 2p)/3)^4 =
(3^4)((-1^3)(7 - 2p)^3) / (9^3)(7 - 2p)^4 =
(3^4)(-1) / (3^6)(7 - 2p) =
-1 / (3^2)(7 - 2p) =

-1 / (9(7 - 2p))

2007-01-11 15:42:22 · answer #3 · answered by Helmut 7 · 0 0

1. ans=1

2.i don't know what u mean of 7-2p/3
if its (7-2p)/3
then
1/(9*(2x-7))

if its 2p - (7/9)
then:
ans = (18p-7)^3 / (9*(2x-21)^4)

2007-01-11 15:19:34 · answer #4 · answered by electro_nnn 2 · 0 1

fedest.com, questions and answers